Prediction of success factors of FMCG commercials using signal processing and machine learning algorithms - Saquib, Nazmus; Mithun, Kaniz Fatema; Tasnim, Jarin; Sen, Pushpol (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.